GENETIC PREDISPOSITION TO HEMATOLOGIC MALIGNANCIES IN CHILDHOOD AND ADOLESCENCE - Francesco Fabozzi; Angela Mastronuzzi (Mediterranean Journal of Hematology and Infectious Diseases)
Advances in molecular biology and genetic testing have greatly improved our understanding of the genetic basis of hematologic malignancies and have enabled the identification of new cancer predisposition syndromes. The recognition of a germline mutation in a patient affected by a hematologic malignancy allows for a tailored treatment approach in order to minimize toxicities, and informs the donor selection for hematopoietic stem cell transplantation as well as the comorbidities evaluation and surveillance strategies.